ҚАРАҚАЛПАҚ ТИЛИНДЕГИ ПЕРИФРАЗАЛАРДЫҢ ТЕМАТИКАЛЫҚ ТОПАРЛАРЫ - Пирниязова, А.К.; Каллибекова, Г.П. (FAN va JAMIYAT, 2024)
The article is devoted to one of the figurative and expressive means - periphrases, used in the Karakalpak language. Periphrases of the language of poetry and journalism are analyzed and divided into thematic groups.